Residual stress, microstructure and micro-hardness evolution of laser powder bed fusion Ti6Al4V: Effect of stress relief annealing - Zhongxu Xiao; Xu Luo; Pan Liu; Guanjun Fu; Jun Wang; Guangxuan Zhou; Xiaojia Nie; Yang Qi; Haihong Zhu (Journal of Materials Research and Technology)
Stress relief annealing serves as a critical post-processing in laser powder bed fusion (LPBF) of Ti6Al4V alloy to release the inherited residual stress. However, most researches on the heat treatment of Ti6Al4V alloy in LPBF mainly focused on the high-temperature stress-relief annealing to regulate the microstructure and mechanical properties. The research on the low-temperature stress-relief annealing which has a low impact on the microstructure is relatively few. In this study, the effect of the low-temperature stress-relief annealing at 350 °C on the residual stress behavior, microstructure and micro-hardness evolution were investigated systematically, with comparisons to conventional annealing treatments at 500–650 °C. The results indicated that the residual stress can be almost released at the low-temperature annealing of 350 °C with duration of 600 min, and the composition phases don't decompose with the duration extending. When treated with the high-temperature annealing of 500 °C and 650 °C, the white β phase began to precipitate and its fraction increases with the duration extending. Due to the partial decomposition of the acicular α′ phase in the as-built specimens to form smaller substructures, the micro-hardness of the annealed specimens is consistently higher than that of the as-built specimens. The micro-hardness reaches the highest at the annealing temperature of 500 °C with the duration of 10 min.